The Correlation between Perceptions and Compliance in the Use of Personal Protective Equipment of Nurses at RSU Haji Surabaya - Rika Mudrikah Miftakhul Janah; Tri Martiana (Universitas Airlangga, 2021)
Introduction: According to previous studies, the level of compliance with the use of personal protective equipment of the nurses at RSU Haji Surabaya was still quite low. Only 17.8% of the nurses were compliant in using masks, whereas 82.2% of the nurses were not. Moreover, 57.8% nurses were compliant in using medical gloves, whereas 42.2% were not. The purpose of this study is to analyze the relationship between perception and compliance with the use of personal protective equipment of the nurses at at RSU Haji Surabaya. Methods: This study was an observational and cross-sectional study. The population used in this study was the nurses who served in the operating and lung room of at RSU Haji Surabaya. Total sampling technique was used to 33 samples. Moreover, the data were taken by questionnaires and observations. Data analysis was performed by coefficient contingency test by looking at the value of C. Results: The results show that 85.7% of nurses in the operating room are non-compliant and 33.3% nurses in the lung room are non- compliant with the use of PPE. The results also showthat the perception variable that has the strongest relationship with compliance is perception of severity (C = 0.312). Conclusion: The closest relationship between the two variables are the relationship of compliance of PPE usage with the gender of nurses, and the determination of nurses' perceptions is based on the Health Belief Model approach.Keywords: compliance, nurse, perception, personal protective equipment